Functional neuroanatomy of executive function after neonatal brain injury in adults who were born very preterm. - Anastasia K Kalpakidou; Matthew P G Allin; Muriel Walshe; Vincent Giampietro; Philip K McGuire; Larry Rifkin; Robin M Murray; Chiara Nosarti (PLoS ONE)
Individuals who were born very preterm (VPT; <33 gestational weeks) are at risk of experiencing deficits in tasks involving executive function in childhood and beyond. In addition, the type and severity of neonatal brain injury associated with very preterm birth may exert differential effects on executive functioning by altering its neuroanatomical substrates. Here we addressed this question by investigating with functional magnetic resonance imaging (fMRI) the haemodynamic response during executive-type processing using a phonological verbal fluency and a working memory task in VPT-born young adults who had experienced differing degrees of neonatal brain injury. 12 VPT individuals with a history of periventricular haemorrhage and ventricular dilatation (PVH+VD), 17 VPT individuals with a history of uncomplicated periventricular haemorrhage (UPVH), 13 VPT individuals with no history of neonatal brain injury and 17 controls received an MRI scan whilst completing a verbal fluency task with two cognitive loads ('easy' and 'hard' letters). Two groups of VPT individuals (PVH+VD; n = 10, UPVH; n = 8) performed an n-back task with three cognitive loads (1-, 2-, 3-back). Results demonstrated that VPT individuals displayed hyperactivation in frontal, temporal, and parietal cortices and in caudate nucleus, insula and thalamus compared to controls, as demands of the verbal fluency task increased, regardless of type of neonatal brain injury. On the other hand, during the n-back task and as working memory load increased, the PVH+VD group showed less engagement of the frontal cortex than the UPVH group. In conclusion, this study suggests that the functional neuroanatomy of different executive-type processes is altered following VPT birth and that neural activation associated with specific aspects of executive function (i.e., working memory) may be particularly sensitive to the extent of neonatal brain injury.